Amine‐Activated Iron Catalysis: Air‐ and Moisture‐Stable Alkene and Alkyne Hydrofunctionalization. Issue 15 (11th July 2016) - Challinor, Amy J.; Calin, Marc; Nichol, Gary S.; Carter, Neil B.; Thomas, Stephen P.
Abstract: A simple alkylamine [( i Pr)2 NEt] has been used to activate an air‐ and moisture‐stable iron(II) pre‐catalyst for alkene and alkyne hydrofunctionalization reactions. This amine activation has enabled the highly operationally simple hydrosilylation and hydroboration of alkenes and alkynes using just 0.25–2 mol% iron catalyst and 1–25 mol% amine. Significantly, these reactions proceed in equal yield under both air and inert reaction conditions. Abstract :